The Struggle for Soviet Jewry in American Politics: Israel versus the American Jewish Establishment - Lazin, Fred A. (Lexington Books, 2005)
Until 1989 most Soviet Jews wanting to immigrate to the United States left on visas for Israel via Vienna. In Vienna, with the assistance of American aid organizations, thousands of Soviet Jews transferred to Rome and applied for refugee entry into the United States. The Struggle for Soviet Jewry in American Politics examines the conflict between the Israeli government and the organized American Jewish community over the final destination of Soviet Jewish ZmigrZs between 1967 and 1989. A generation after the Holocaust, a battle surrounded the thousands of Soviet Jewish ZmigrZs fleeing persecution by choosing to resettle in the United States instead of Israel. Exploring the changing ethnic identity and politics of the United States, Fred A. Lazin engages history, ethical dilemma, and diplomacy to uncover the events surrounding this conflict. This book is essential reading for students and scholars of public policy, immigration studies, and Jewish history.